(untitled) (Biological Sciences - PJSIR, 1995)
Eight wheatgenotypesweretestedforcaryopseswateruptake,germinationandseedlinggrowthunderPEG-6000 induced water stress (0.0, -0.50, -0.75, and -1.100 MPa). Caryopses were surface sterilized and planted on moistened filterpaperwiththerespectivesolutionsin9em petri-dishesandinglassjars overnylonnet.Afterplanting,petri-dishes or glass bowls were placed in a growth chamber maintained at 30125°Cday/night temperature and 16hrphotoperiod. Wateruptakereachedapeakvaluewithin24-30hrinal genotypesunderal waterstressconditions.Water imbibition, germination percentage and seedling growth decreased with concomitent reduction in water potential of the medium. The genotypes, Chakwal-86, DS-4,Barani-83andC-228 performedcomparativelybetterthanDS-17,Pavon, LU-26S and Sarsabz under our experimental conditions.